2015
DOI: 10.1016/j.amjsurg.2014.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Racial variation in the use of life-sustaining treatments among patients who die after major elective surgery

Abstract: Background Although various studies have documented increased Life-Sustaining Treatments (LST) among racial minorities in medical patients, whether similar disparities exist in surgical patients is unknown. Methods Retrospective cohort study using the Nationwide Inpatient Sample (2006–2011) examining patients >39 years who died following elective colectomy. Primary predictor variable was race and main outcome was use of LST. Results In univariate analysis, significant differences existed in use of CPR (Bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 29 publications
0
14
1
Order By: Relevance
“…In this retrospective, registry-based study of adults diagnosed with metastatic prostate, lung, breast, and colon cancer, there were significantly lower odds of receiving palliative care among patients treated at MSHs compared with non-MSHs. Although it has been previously reported that minority patients are less likely to receive palliative care services at the end of life, 8 , 9 the present findings suggest that site of care may be a significant factor associated with race/ethnicity-based differences in palliative care.…”
Section: Discussioncontrasting
confidence: 71%
“…In this retrospective, registry-based study of adults diagnosed with metastatic prostate, lung, breast, and colon cancer, there were significantly lower odds of receiving palliative care among patients treated at MSHs compared with non-MSHs. Although it has been previously reported that minority patients are less likely to receive palliative care services at the end of life, 8 , 9 the present findings suggest that site of care may be a significant factor associated with race/ethnicity-based differences in palliative care.…”
Section: Discussioncontrasting
confidence: 71%
“…13, 20–22 However, most studies describing patterns of end-of-life care for patients with kidney disease have either focused exclusively on older adults or did not present age-stratified results. 12, 15 While life expectancy is shortest and the prevalence of frailty highest for older patients with ESRD, differences in life expectancy compared with the general population are most marked for younger dialysis patients and their prevalence of frailty is much higher than for the general population.…”
Section: Discussionmentioning
confidence: 99%
“…However, a deeper understanding of conceptions and attitudes in the decision‐making process is still, to a large extent, lacking. Patient factors that contribute to variabilities in EoL decisions include the patient's medical condition, the diagnosis, advanced age, poor baseline functional status and female sex …”
Section: Introductionmentioning
confidence: 99%
“…Patient factors that contribute to variabilities in EoL decisions include the patient's medical condition, the diagnosis, advanced age, poor baseline functional status and female sex. [9][10][11][12][13][14][15][16][17] In Sweden, the Swedish National Board of Health and Welfare stipulates regulations about LST and EoL decisions. Physicians are obliged to (a) respect patient autonomy, (b) consult at least one other health professional with a license to practice, prior to making a decision regarding withholding or withdrawing LST and (c) provide detailed documentation of the reasons for the decision.…”
Section: Introductionmentioning
confidence: 99%